Kondisi Sosial Ekonomi Karyawan PT. Tani Prima Makmur - Sani; La Harudu; La Ode Nursalam (Jurusan Pendidikan Geografi FKIP Universitas Halu Oleo, 2023)
Oil palm plants have an important meaning in the development of national plantations in Indonesia. The aims of this research are: 1) to describe the social condition of employees of PT. Tani Prima Makmur; and 2) describe the economic condition of employees of PT. Tani Prima Makmur. This type of research is descriptive qualitative. Determination of respondents in the study using simple random sampling technique with a total of 32 respondents. The results showed that: 1) the social condition of employees has a relatively good level of education with the last level of education being at the high school level, the health condition of employees is also quite good, social interaction among employees is going well; and the housing conditions for the employees are very good where most of the employees already have their own houses, the walls of the buildings are permanent, have SEC lighting, and use PDAM clean water sources; 2) the economic condition is quite good with employee income ranging from Rp. 2,552,014 - Rp. 4000,000 with an average income of Rp. 3,457,005/month and employee expenses are relatively high with an average expenditure of Rp.2,078,125/month.